2017
DOI: 10.1097/psy.0000000000000466
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness Meditation Training and Executive Control Network Resting State Functional Connectivity: A Randomized Controlled Trial

Abstract: Objective Mindfulness meditation training has been previously shown to enhance behavioral measures of executive control (e.g. attention, working memory, cognitive control), but the neural mechanisms underlying these improvements are largely unknown. Here, we test whether mindfulness training interventions foster executive control by strengthening functional connections between dorsolateral prefrontal cortex (dlPFC) - a hub of the executive control network – and frontoparietal regions that coordinate executive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
112
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(126 citation statements)
references
References 79 publications
7
112
0
7
Order By: Relevance
“…71 For example, there is initial evidence that mindfulness interventions can increase resting state functional connectivity of regions known to be important in executive control and top-down regulation. 72,73 We recently showed that mindfulness training increases functional connectivity at rest (i.e., the PCC in the default mode network) with regulatory regions of the PFC (DLPFC), relative to a relaxation training comparison group. 72 The DLPFC is a region implicated in emotion regulation, 63 and as such this connectivity pattern may represent a potential strengthening of top-down executive control after mindfulness training.…”
Section: Behavioral Interventions and The Threat/stress Neural Systemmentioning
confidence: 99%
“…71 For example, there is initial evidence that mindfulness interventions can increase resting state functional connectivity of regions known to be important in executive control and top-down regulation. 72,73 We recently showed that mindfulness training increases functional connectivity at rest (i.e., the PCC in the default mode network) with regulatory regions of the PFC (DLPFC), relative to a relaxation training comparison group. 72 The DLPFC is a region implicated in emotion regulation, 63 and as such this connectivity pattern may represent a potential strengthening of top-down executive control after mindfulness training.…”
Section: Behavioral Interventions and The Threat/stress Neural Systemmentioning
confidence: 99%
“…, suggesting increased dACC activity MBIs also lead to enduring changes in FPCN and DAN, including increased activity in FPCN (dlPFC and posterior parietal cortex [PPC]) during executive processing[65] and emotion regulation tasks[66] following MBSR. Three-days of intensive meditation produced increased connectivity between FPCN, DAN, and VAN[67]. Taken together, these findings suggest MBIs may lead to enduring increases in activity and/or coordination of SN, FPCN, and DAN that possibly underlie increased capacity for meta-awareness of and disengagement with spontaneous internal thoughts and shifting attention toward presentmoment physical sensations[31].Disidentification.…”
mentioning
confidence: 80%
“…Although speculative, taken together, these early findings are suggestive of a mindfulness-entrained brain network configuration characterized by coordinated increased within-network connectivity in FPCN (73) and SN [67] increased cross-network connectivity in FPCN-DMN [27,76,79,80] and FPCN-DAN [67], and altered patterns of cross-network connectivity between DMN and SN [39,76,80] [62,85], increased dmPFC-IPL connectivity [78], and increased dmPFC-insula anti-correlation [86]. Long-term meditation and MBIs also appear to lead to enduring alterations in the MTL-DMN, including greater hippocampal grey matter density [52, [87][88][89] and increased resting connectivity between hippocampus and PCC [85].…”
Section: Effects Of Mindfulness On Proposed Metacognitive Processes Imentioning
confidence: 99%
“…Furthermore, body scans-mostly integrated in a mindfulness-based stress reduction program (MBSR [46])-may support the restructuring of the brain volume and biochemical deteriorations that affect pain patients [47]. As it was shown that MBSR is powerful in increasing stress resilience [48], this association may additionally reinforce the intended pathways through the combination of exercise and distraction [49]. Because stress and pain stimuli are processed in the same brain areas, additional effects on central and peripheral sensitization may therefore be expected [14].…”
Section: Rationale Of Selectionmentioning
confidence: 99%